AN INSIGHT INTO THE USE OF COMPLEMENTARY AND ALTERNATIVE MEDICINES AMONG PATIENTS WITH ATOPIC ECZEMA IN CENTRAL DURBAN, SOUTH AFRICA - Thandar, Yasmeen; Botha, Julia; Sartorius, Benn; Mosam, Anisa (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Complementary and alternative medicines (CAM) are increasingly popular globally with frequent useamongst patients with atopic eczema (AE). Despite increased AE prevalence in South Africa (SA), no local data onCAM-use for this disease exists.Methods: A cross-sectional study utilizing a comprehensive questionnaire qualifying and quantifying CAM use inpatients with AE. We interviewed 206 AE patients; 106 from a public hospital dermatology clinic and 100 from privatedermatology practices in central Durban. One-way analysis of variance (ANOVA) compared means of continuouspredictors across 3 or more groups. Differences in frequencies of categorical explanatory variables by CAM and AEwere assessed using Pearson chi-square (χ2) test or Fishers exact test.Results: There were 143 children, 63 adults; 163 females and 43 males. Races represented were Black (56%), Indian(33%), Coloured (6%) and White (4%). 135(66%) reported current or previous CAM use. Common reasons werefamily/friends’ recommendations (42%) and media-influence (23%). Frequently used CAMs were vitamins (35%),aromatherapy oils (27%), herbal creams (26%), traditional African medicines (23%) and homeopathy (19%). Nondisclosureto the dermatologist was high (59%). Almost half (48%) said they were not questioned about CAM use.More Indian patients used CAM (p=0.001) and Muslims were most frequent CAM users (p=0.044). Although notstatistically significant, the more educated and higher income bracket used CAM more. 28% felt CAM had fewer sideeffects,28% felt it was safer than conventional medicine and 35% felt CAM was more natural.Conclusion: The detailed trends of CAM use by South Africans for AE is an important addition to the currentliterature. Dermatologists and healthcare professionals addressing patients with AE need to be more familiar with CAMtypes that patients may explore as this could impact on the overall clinical outcome.